2010
DOI: 10.1016/j.drugalcdep.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin improves cold-pressor pain responses in methadone-maintained patients

Abstract: Individuals on methadone maintenance for the treatment of addiction (MM) are demonstrated to be hyperalgesic to cold-pressor pain in comparison to matched controls and ex-opioid addicts, a finding described as clinical evidence of opioid-induced hyperalgesia (OIH). Interestingly, opioids induce hyperalgesia via many of the same neuro-inflammatory and central sensitization processes that occur with the development of neuropathic pain. Evaluated in this study was the efficacy of a key pharmacotherapy for neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 103 publications
0
54
0
2
Order By: Relevance
“…Thus far, a host of animal studies have found that OIH is reversible by the NMDA receptor antagonists MK-801 [31,42,[160][161][162][163][164][165], ketamine, or traxoprodil [93]. Human studies have found similar results by adding adjuvant ketamine [46,54,88,166], as well as gabapentinoids such as pregabalin [49,55] or gabapentin [23], or the cyclooxygenase-2 inhibitor parecoxib [48,167], as reviewed in the subsequent sections. However, more recent research has shown that manipulating these substrates does not unequivocally resolve OIH.…”
Section: Prospective Treatments For Oihmentioning
confidence: 86%
See 4 more Smart Citations
“…Thus far, a host of animal studies have found that OIH is reversible by the NMDA receptor antagonists MK-801 [31,42,[160][161][162][163][164][165], ketamine, or traxoprodil [93]. Human studies have found similar results by adding adjuvant ketamine [46,54,88,166], as well as gabapentinoids such as pregabalin [49,55] or gabapentin [23], or the cyclooxygenase-2 inhibitor parecoxib [48,167], as reviewed in the subsequent sections. However, more recent research has shown that manipulating these substrates does not unequivocally resolve OIH.…”
Section: Prospective Treatments For Oihmentioning
confidence: 86%
“…Several studies have demonstrated OIH in patients enrolled in methadone maintenance treatment [23,43,[57][58][59][60]. However, other studies have documented a reduction in OIH after patients were rotated onto methadone treatment.…”
Section: Other Nmda Receptor Antagonistsmentioning
confidence: 96%
See 3 more Smart Citations